Mental Workload and Work Stress among Train Drivers and Their Associated Factors: A Cross-Sectional Study in Indonesia - Marizca Saras Chitra Hidayat; Ahmad Fuady; Suryo Wibowo; Dewi Soemarko; Nuri Purwito Adi (The Indonesian Journal of Community and Occupational Medicine, 2025)
Background: Employment in the railway sector is one of the professions that involves high challenges and demands, as it requires handling various complex tasks and responsibilities to ensure the safety and comfort of passenger travel. Train driver and train co-driver bear a high workload and face complex mental demands, making them vulnerable to work stress.Objective: This study aims to examine the relationship between mental workload and work stress, as well as occupational and sociodemographic factors among train driver and train co-driver in DAOP 2 Bandung.Methods: A cross-sectional analytical observational study was conducted using data from routine medical check-ups. Mental workload was measured using the NASA-TLX questionnaire, while work stress was assessed using the Job Stress Scale (JSS).Results: Among 106 participants, 53% experienced high mental workload, while 97% reported low to moderate work stress. No significant associations were found between work stress and mental workload (p=0.190), job type, years of service, age, marital status, income, number of dependents, or coworker support. However, work stress was significantly associated with role expectation conflict (p<0.001) and work-life balance (p=0.029). After multivariate analysis, only role expectation conflict remained significantly associated. Workers experiencing moderate to high role expectation conflict had a 14.3-fold higher risk of work stress (CI 4.45–46.17).Conclusion: Role expectation conflict is a significant factor associated with work stress. Addressing psychosocial factors through clear role definitions and policies supporting work-life balance is essential in reducing stress among train crews.